Studies On Side Effect Profile Of Treated Hypertensives On Selected Pharmacotherapy - Ismail, Marina (2001)
Hypertension is a major public health problem because of its consequences. Its treatment is crucial and goals include to decrease ~orbidity and mortality associated with hypertension by decreaSing blood pressure using drugs that have good tolerance, dosing convenience and low cost. As many antihypertensives are now available, it is important to choose the most appropriate drug in terms of efficacy and with least side effect in order to improve compliance and the patient's quality of life. In HUSM, metoprolol is a widely used. Its metabolism is mediated by the polymorphic debrisoquinehydroxylase that exhibits large inter ethnic difference. As most of its adverse reactions could be due to excessive plasma concentrations, its use among our local population may therefore be associated with adverse effects due to reduced capacity of the local population to metabolise the drug. The objedives of this study were therefore to investigate the use of metoprolol in the treatment of hypertension in relation to the incidence of adverse drug reactions it caused. We would also determine whether patients who experienced adverse reactions suffered reduced quality of life. As controls, we used patients who received enalapril or enalapril combined with metoprolol in the treatment of their hypertension.